2014
DOI: 10.1038/srep04694
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: JNK confers 5-fluorouracil resistance in p53-deficient and mutant p53-expressing colon cancer cells by inducing survival autophagy

Abstract: Deficiency or mutation in the p53 tumor suppressor gene commonly occurs in human cancer and can contribute to disease progression and chemotherapy resistance. Currently, although the pro-survival or pro-death effect of autophagy remains a controversial issue, increasing data seem to support the idea that autophagy facilitates cancer cell resistance to chemotherapy treatment. Here we report that 5-FU treatment causes aberrant autophagosome accumulation in HCT116 p53−/− and HT-29 cancer cells. Specific inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 36 publications
2
72
0
Order By: Relevance
“…For instance, inhibition of MEK1/2 enhanced the radiosensitizing effects mediated by 5-FU in vitro and in vivo [45]. Further, JNK activity has been reported to prompt autophagy, protecting colon cancer cells with impaired p53 function from 5-FU cytotoxic effects, which in turn was shown to be reversed following JNK inhibition [46]. Instead, the p38MAPK pathway was shown to be activated in response to 5-FU, controlling cell fate by shifting the balance between apoptosis and autophagy towards increased 5-FU sensitivity [47].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, inhibition of MEK1/2 enhanced the radiosensitizing effects mediated by 5-FU in vitro and in vivo [45]. Further, JNK activity has been reported to prompt autophagy, protecting colon cancer cells with impaired p53 function from 5-FU cytotoxic effects, which in turn was shown to be reversed following JNK inhibition [46]. Instead, the p38MAPK pathway was shown to be activated in response to 5-FU, controlling cell fate by shifting the balance between apoptosis and autophagy towards increased 5-FU sensitivity [47].…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, researchers have focused on the relationship among apoptosis, drug resistance and autophagy in cancer cells. Various studies have demonstrated that increased induction of autophagy can become a mechanism of allowing tumor cells to survive the conditions of hypoxia, acidosis or chemotherapy, which results in a decrease in apoptosis and drug resistance (24,25). There are also other studies indicating out that autophagy inhibitors in combination with chemotherapeutic agents may provide a premise for the treatment of colorectal cancer (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in response to irinotecan, pro-survival autophagy was induced by activating MAPK14/p38 signaling, which lead to drug resistance [108]. It is likely that protective autophagy in 5-FU resistance occurs through JNK activation [109]. Additionally, bortezomib and enzalutamide, which are androgen receptor signaling inhibitors (ARSIs), activate AMPK-dependent autophagy and provide therapeutic resistance [110,111].…”
Section: Therapy Resistance and Autophagymentioning
confidence: 97%